Health outcomes of lifestyle treatment for patients with obesity before and during the COVID-19 pandemic—a retrospective pre-post study - Alizadeh, Sadegh; Grindheim, Sophie; Klöckner, Christian A.; Følling, Ingrid S. (Frontiers in Public Health, 2025)
BackgroundIn Norway, one treatment option for patients with obesity has been a multi-component lifestyle program with a continuous stay at rehabilitation centers. During the COVID-19 pandemic, these stays were reduced, and digital follow-up for patients from home was introduced. How these changes affected patients’ health outcomes after treatment is unknown. This study aimed to investigate health outcomes for patients who attended lifestyle treatment and to compare patients who attended treatment before COVID-19 with patients who attended during COVID-19.MethodA retrospective pre-post design was used. A total of 103 patients (mean age 45.4 years, 64% women) with a mean Body Mass Index (BMI) of 42.3 kg/m2 were included of whom 53 attended treatment before COVID-19 and 50 attended treatment during COVID-19. Health outcomes measured were BMI, Physical Activity (PA) levels, and Health-Related Quality of Life (HRQoL). Data were collected at baseline and after 9 weeks of treatment for both groups.ResultsAll patients had a significant reduction in BMI after treatments, with no differences between the groups. PA levels and HRQoL increased for both groups, however, the group that attended treatment before COVID-19 had significantly higher PA levels and HRQoL (p < 0.001) than the group that attended during COVID-19.ConclusionThis study demonstrates that structured lifestyle treatment supports improvements in BMI, HRQoL, and PA levels, even with reduced in-person contact. Although differences were observed between treatment periods, further research is needed to understand how the delivery mode and specific components of digital and in-person treatments affect health outcomes, providing insights to optimize future lifestyle interventions for individuals with obesity.